The Implementation of Scientific Approach in Online Teaching Reading Comprehension at Mtsn2 Medan - Elvi Yosna Lubis; Masitowarni . Siregar; Sumarsih . Sumarsih (Universitas Negeri Medan, 2022)
This study focused on the investigation of implementing Scientific Approach in teaching online reading comprehension at MTsN 2 Medan. The research problem was based on the implementation of Scientific Approach as one of teaching strategies in the application of curriculum 2013 in selected school. Scientific Approach consists of several stages which somehow were not applied optimally in teaching and learning activity. The research was conducted by using qualitative descriptive design. The data were collected by observing and interviewing subjects of the study.The subjects were three teachers who used to teach reading comprehension at MTsN 2 Medan in grade eight in junior high school education level. The objectives of the research were to find out; 1) the implementation of scientific approach in online teaching reading, 2) how the strategies are realized to be implemented in online teaching reading, 3) the reason of the strategies of implementing scientific approach are realized in online teaching reading. Based on the analysis of the data. The findings of the research were: 1) teachers had applied the implementation even though it was not optimal, 2) the strategies used of the approach in order to encourage students during learning process, 3) teachers had reasons to implement scientific approach (observing, questioning, experimenting, associating, and communicating) as a teaching strategy. The result of the research would be a reference towards further study and help other teachers in applying teaching strategy of learning process